ANALISIS PENERAPAN REKAM MEDIS ELEKTRONIK DI PUSKESMAS PUTRI AYU KOTA JAMBI DENGAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Intan Permata; Muldiasman Muldiasman; Adila Solida; Arnild Augina Mekarisce (Jurnal Penelitian Kesmasy, 2026)
The development of information technology in the health sector encourages primary healthcare facilities, such as community health centers, to transition from manual recording systems to Electronic Medical Records (EMR). However, the success of EMR implementation is not only determined by the availability of technology but also by the level of user acceptance of the system. The PMK Regulation 24 of 2022 states that every healthcare facility is required to implement electronic medical records. The purpose of this research is to analyze the implementation of Electronic Medical Records at Puskesmas Putri Ayu in Jambi City using the Technology Acceptance Model (TAM) approach. The research method used is descriptive qualitative, with data collection techniques thru in-depth interviews and direct observation. The subjects of this research are the Head of the Community Health Center, medical record officers, doctors, dentists, nurses, midwives, laboratory officers, pharmacists, and the Head of Administration. The object of this research is the Electronic Medical Record (EMR) using the Technology Acceptance Model (TAM) method. This research is reviewed from three aspects, namely perceived ease of use, perceived usefulness, and behavioral intention to use. According to the research findings, the implementation of Electronic Medical Records (EMR) at Puskesmas Putri Ayu shows positive results, as it is considered easy to use, beneficial in improving efficiency and service quality, and receives strong support from healthcare workers for sustainable use despite some technical challenges. Overall, it can be concluded that the implementation of EHR is very important to ensure it runs smoothly and as planned, including minimizing existing obstacles or issues and also improving the system to be better.